2020
DOI: 10.1038/s41598-020-62507-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and genomic analysis for cocoon yield traits in silkworm

Abstract: Domestic species provides a powerful model for examining genetic mechanisms in the evolution of yield traits. the domestic silkworm (Bombyx mori) is an important livestock species in sericulture. While the mechanisms controlling cocoon yield are largely unknown. Here, using B. mori and its wild relative B. mandarina as intercross parents, 100 BC 1 individuals were sequenced by restriction site-associated DNA sequencing (RAD-Seq). The linkage map contained 9,632 markers was constructed. We performed high-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Under long-term artificial selection, B. mori acquired various characteristics suitable for sericulture. For example, the weight of the cocoon shell of B. mori is much higher than that of B. mandarina (Ômura 1950, Li et al 2017, Fang et al 2020). In addition, B. mori moths lost their flying ability due to the degeneration of their flight muscles and a reduction in wing stiffness (Lu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under long-term artificial selection, B. mori acquired various characteristics suitable for sericulture. For example, the weight of the cocoon shell of B. mori is much higher than that of B. mandarina (Ômura 1950, Li et al 2017, Fang et al 2020). In addition, B. mori moths lost their flying ability due to the degeneration of their flight muscles and a reduction in wing stiffness (Lu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of lethality is likely to continue to impede the genetic analysis of pigmentation loss and other domestication-associated traits in B. mori. Recently, several candidate genes associated with domestication in B. mori have been identified using quantitative trait locus (QTL) mapping, including silk production (Li et al 2017, Fang et al 2020, larval climbing ability (Wang, Lin, et al 2020), and mimicry (Wang, Lin, et al 2020). In addition, a recent population genetic analysis identified 300 candidate genes as targets of recent selection in B. mori, some of which are likely to be associated with silk production and voltinism (Xiang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, transcriptome and proteomics methods have been used to screen genes related to CSW, which plays an important role in guiding the study of genes related to silk yield (Ma et al 2014;Wang et al 2014;Fang et al 2015;Li et al 2016;Peng 2016;Luan et al 2018). Fang et al also screened related genes that regulate the silk yield through genomic analysis (Fang et al 2020). However, owing to the uncertainty of omics analysis, researchers are still trying to map the major genes through forward genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Research shown that silkworms may have been initially domesticated in China as tri-moulting lines, then subjected to independent spreads along the Silk Road that gave rise to the development of most local strains, and further improved for modern silk production in Japan and China, having descended from diverse ancestral sources (Lu et al, 2002;Pan et al, 2008;Sun et al, 2012;Xia et al, 2009;Xiang et al, 2018). Without artificial selection and live in the wild, wild silkworm preserved abundant genetic diversity, and shown significant differences in cocoon quality, disease resistance, stress tolerance, growth and development when compared with domestic silkworm, so it could be germplasm resources of genetic improvement of domestic silkworm (Fang et al, 2020;Fang et al, 2015;Xiang et al, 2013;Zhang et al, 2015). The origin and domestication of Bombyx mori and Bombyx mandarina are basic scientific issues in sericulture, and also involve in the inheritance of the silk culture.…”
mentioning
confidence: 99%